2019
DOI: 10.32615/ps.2019.106
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characterization and thylakoid ultrastructure analysis in super high-yield hybrid rice leaves under drought stress

Abstract: Rice serves for more than a third of the world's population. However, drought stress (DS) affects its growth and yield. In order to understand plant drought adaptability, we explored the physiological and thylakoid ultrastructural alteration in super high-yield hybrid rice Liangyoupeijiu (LYPJ) under DS. Results showed that DS altered the thylakoid ultrastructure; twisted and fractured stroma thylakoids and more starch granules in chloroplast of LYPJ were present. Also, DS lowered chlorophyll and carotenoid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Such studies have demonstrated similarities in crops, such as canola (Brassica napus L.) and sunflower (Helianthus annuus L.) (Sun et al 2010). In addition, it has also been found that under water stress, the metabolism of crops is disrupted and plant growth is restricted (Waraich et al 2011, Shao et al 2016, which may also explain the changes in morphology during water stress. Chl, the main photosynthetic pigment in plant leaves, is an important indicator used for evaluating the physiological status of plants; it is also an important indicator reflecting the photosynthetic capacity of leaves (Xu et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies have demonstrated similarities in crops, such as canola (Brassica napus L.) and sunflower (Helianthus annuus L.) (Sun et al 2010). In addition, it has also been found that under water stress, the metabolism of crops is disrupted and plant growth is restricted (Waraich et al 2011, Shao et al 2016, which may also explain the changes in morphology during water stress. Chl, the main photosynthetic pigment in plant leaves, is an important indicator used for evaluating the physiological status of plants; it is also an important indicator reflecting the photosynthetic capacity of leaves (Xu et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…With global climate change, the shortage of freshwater resources and the imbalanced distribution of water are becoming more serious each year, and water stress has become the main factor limiting global agricultural production (Tambussi et al 2005, Khan et al 2016. Furthermore, because of the variation in precipitation in recent years, the area of land suffering from water stress is gradually increasing (Kataria et al 2015, Wang et al 2019a. Water stress may arise as a result of waterlogging or water deficit (Guo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought is one of the harshest abiotic factors inhibiting photosynthesis and thereby restricting plant growth and yield (Alam et al, 2021;Panda et al, 2021). Drought stress limits the efficiency of the photosynthetic apparatus, resulting in substantial damage to the thylakoid membranes, and decrease in photosynthetic pigments (Velikova et al, 2016;Wang et al, 2019). To ensure survival under such an extreme environment, plants employ their own defense system, such as reduced transpiration rate by closing stomata (Rangani et al, 2018;Xi et al, 2018;Yang et al, 2021).…”
Section: Contribution Of Inorganic Ions To Osmotic Adjustment In H Glomeratus Under Drought and Salt Stress Alone Or In Combinationmentioning
confidence: 99%
“…Drought stress significantly inhibits the growth of plants because it can cause the Communicated by H. Peng. accumulation of reactive oxygen species (ROS), destroy the chloroplast structure, break the thylakoid matrix, decrease the chlorophyll content (Wang et al 2019b), reduce the activity of related enzymes in the photosynthetic carbon reduction cycle (Ramachandra Reddy et al 2004), change the regulation of chloroplast proteins (Chang et al 2019), and reduce the photosynthetic rate (Nxele et al 2017;Khan et al 2019).…”
Section: Introductionmentioning
confidence: 99%